The impact of sensory integration therapy on gross motor function in children after prenatal exposure to alcohol - Wilczyński, Jacek; Zawada, Katarzyna (Medical Studies/Studia Medyczne, 2015)
Introduction : In Poland there are 900 cases of full-blown foetal alcohol syndrome (FAS) in neonates per year, and in 9000 children there are some symptoms of it. Aim of the research : To analyse the impact of sensory integration (SI) therapy on gross motor skills function in children after prenatal exposure to alcohol. Material and methods: The study was conducted on a group of 20 children aged 4–5 years with information from an interview about prenatal exposure to alcohol. The diagnosis of sensory integration disorder consisted of two 60-minute diagnostics meetings. Twelve trials with clinical observations were performed by Ayres: finger to nose, cocontraction, prone extension posture, flexed position supine, asymmetrical tonic neck reflex (ATOS), symmetrical tonic neck reflex (STOS), muscle tension, Schilder test, dynamic balance, static balance, gravitational insecurity, and trunk stabilisation. The therapeutic program included: normalisation of the vestibular and proprioceptive system, normalisation of the touch system, strengthening muscle tension, development of motion planning, development of oculomotor performance, development of motor coordination, hand therapy, integration of ATOS, STOS, development of locomotion and balance functions, and improving efficiency of gross and small motor skills. Results and conclusions : High efficiency of SI therapy has been shown in children after prenatal exposure to alcohol on the example of gross motor skills. Positive effects of SI therapy have been shown for tests: finger to nose, in the erect position on the stomach, the flexural position on the back, ATOS, STOS, Schilder test, dynamic balance, static balance, and the uncertainty of gravity and trunk stabilisation. Only cocontraction and muscle tension tests showed no efficacy of SI therapy. The a-Cronbach position analysis showed high reliability of the performed tests both before and after the therapy. It is advisable to continue the study on a larger sample and observation of the functional status of children after therapy.